2014
DOI: 10.1073/pnas.1414780111
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunction of dendritic cells in aged C57BL/6 mice leads to failure of natural killer cell activation and of tumor eradication

Abstract: The reciprocal activation of dendritic cells (DCs) and natural killer cells (NKs) plays a key role in both innate and adaptive immunity. The effect of aging on this cross-talk, a critical step in virus disease control and tumor immunology, has not been reported. Splenic DCs and NKs were purified from both young and old C57BL/6 mice and cocultured in the presence of polyinosinic:polycytidylic acid (poly I:C). The resulting activation of NKs was measured as expression of CD69 and secretion of IFN-γ. However, DCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…In contrast, IL-18 is significantly decreased in the serum of Wrn Δhel/Δhel mice compared to WT animals, whereas Wrn -/- mice showed a similar trend. A lower secretion of IL-18 has been shown to be an important factor in the dysfunction of dendritic cells in aged C57BL/6 mice [ 40 ]. Dendritic cells are central in regulating both innate and acquired immunity.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, IL-18 is significantly decreased in the serum of Wrn Δhel/Δhel mice compared to WT animals, whereas Wrn -/- mice showed a similar trend. A lower secretion of IL-18 has been shown to be an important factor in the dysfunction of dendritic cells in aged C57BL/6 mice [ 40 ]. Dendritic cells are central in regulating both innate and acquired immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic alcohol consumption in animals blunts the ability of DCs to up-regulate costimulatory molecules [227,[232][233][234][235]. In aged animals and humans, the production of proinflammatory cytokines by DCs, including type I IFNs, IL-6, and TNF-a, are decreased, but the level of the anti-inflammatory cytokine IL-10 is greater than in younger hosts [44,222,[236][237][238][239][240][241]. However, not all studies support the conclusion that DCs from older hosts are unable to promote inflammation; some studies have reported no difference in the production of those cytokines with age, or an even an increase in IL-6 and TNF-a by DCs from older, compared with younger, humans and rodents [46,214,217,[242][243][244].…”
Section: Dcsmentioning
confidence: 99%
“…Nevertheless, a growing body of research indicates that the therapeutic activity of DC cancer vaccination does not exclusively rely on engagement of the adaptive immune arm, but also on its ability to harness innate anti-tumor effector cells [ 4 , 5 ]. The importance of NK cells in the anti-tumor activity of DC-based immunotherapy has been demonstrated in several animal studies, some of which have pointed to an indispensable role for NK cells in this respect [ 11 18 ]. In human clinical trials [ 19 21 ], the induction of NK cell immune responses by DC vaccination was shown to be associated with favorable clinical outcome, whereas such correlation has not been consistently reported for DC vaccine-induced T-cell immunity.…”
Section: Introductionmentioning
confidence: 99%